Closure of Serbian Elementary School in Shkodra in 1934 - Velojić, Dalibor (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
After signing the treaties of Tirana, Albania became the representative of Italy for the Balkans. The activities directed toward the Kingdom of Yugoslavia were determined by Yugoslav and Italian relations, which were rather tense at that period. General negation of Yugoslav presence in Albania was evident in the area of education, and as a result, Serbian schools were closed in territories predominantly inhabited with Serbian people, under the pretext of carrying out reforms. The example of the Serbian elementary school in Shkodra best reflects the effects of Albanian education policy regarding ethnic minorities. Archives of Yugoslavia, department of the Ministry of Education, contains the file (pages of documents) related to this school. This paper is based on the mentioned file, as well as available general literature on Yugoslav Albanian relatio
Keywords: Serbian elementary school in Shkodra; Аlbania; Kingdom of Yugoslavia; education policy